Alianças Estratégicas e Investimento Directo como Instrumentos de Internacionalização - O Caso EPOLI - Miguéns, Cristina Isabel Assis de Morais (2006)
In the context of globalization, in which changes take place at a dizzying pace and are rapidly disseminated, the internationalization of corporations comes out as a natural result, or even an unavoidable outcome, to guarantee competitiveness. The target market of a company is no longer confined to national frontiers. Yet differences which still exist among geographic regions suggest minimizing risks in international expansion. This work is meant to be a comprehensive teaching tool on the issue of internationalization, bringing together in a systematic way the theoretical sources and applying them to the case of a young and dynamic Portuguese corporation with a diversified and successful course in the international scene Epoli.